Laparoskopische Resektion eines Riesenkolondivertikels: Fallbericht und Literaturübersicht - Roch, Paul; Friedrich, Tobias; Bönninghoff, Roderich; Rickert, Alexander Lothar (Der Chirurg, 2017)
BackgroundGiant diverticula are rare complications of diverticular disease. Current opinion regards operative therapy as the method of choice for the treatment of symptomatic giant diverticula; however, there is neither consensus about the technique nor about the necessary extent of resection. Based on a non-systematic review of the literature, an overview of giant diverticula in terms of epidemiology, pathology and classification is given. The current case is considered with respect to appropriate diagnostic procedures and possible therapeutic options.Case presentationAn 80-year-old female patient presented to the emergency department with abdominal pain and dyspnea. A computed tomography scan showed a large gas-filled structure in the upper left abdomen adjacent to the left colon. A giant colonic diverticulum was suspected and laparoscopy was performed. Intraoperatively, the diagnosis of a giant colon diverticulum located at the splenic flexure was confirmed. An unremarkable diverticulosis only was found in the descending colon. The giant diverticulum was treated by an atypical colon wedge resection and the postoperative course was uneventful.DiscussionThis case report describes a laparoscopic atypical colon wedge resection as treatment of a giant colon diverticulum. Only four laparoscopic bowel resections in terms of sigmoid resections or hemicolectomy with primary anastomosis have been reported. Minimally invasive surgery can be a valuable alternative to open procedures. In the current case a laparoscopic atypical colon wedge resection was safely performed. This option might be considered as an alternative to extended resections of giant diverticula. Localization of the giant diverticulum and the simultaneous existence of diverticular disease are the main criteria for the decision between the different operative approaches.